Liturgical Contextualization In Traditional Rituals - Richardson Siwy (Program Pascasarjana UKIM, 2026)
Traditional rituals in society, especially the Kulawi tribe in Central Sulawesi, are an inseparable part of their lives. However, the Kulawi tribe's rituals consist of various symbols and activities: Village cleansing with all traditional prayers (poraeo); harvest or thanksgiving feast (mowunca); traditional wedding (p’memua); Funeral with the determination of the mourning period (Poromu) accompanied by ombo (moratorium containing taboos and prohibitions), placing stones on graves (movatui dayo), and 40-day commemoration (pantaia), which are often ignored in church services, even though these rituals have liturgical and pastoral benefits. With a qualitative approach and a literature review through ritual theory (Catherine Bell) and liturgical contextualization (Peter C. Phan), this article argues that rituals can become liturgical tools through liturgical contextualization efforts, making them useful in church services in the future.